Obstacles on the Road to Palestinian Economic Growth - van der Weide, Roy; Rijkers, Bob; Blankespoor, Brian; Abrahams, Alexei (World Bank, Washington, DC, 2018)
This paper quantifies the impact of market access on local GDP in the West Bank, proxied by nighttime lights, using the deployment of road closure obstacles by the Israeli army between 2005 and 2012 as a quasi-natural experiment generating exogenous temporal and spatial variation in accessibility. Minimum travel times between locality pairs are computed using road network and obstacles data supplemented with information on checkpoint traversal times. These are combined with population data to construct a time-varying market access measure for each locality. Market access has a significant and substantial effect on local light emissions. This association is robust to controlling for conflict, and strengthens when market access is instrumented by the number of obstacles located in a radius between 10 and 25km away from the locality.